2008
DOI: 10.1007/s00268-008-9697-3
|View full text |Cite
|
Sign up to set email alerts
|

Inspection of Safety and Accuracy of D2 Lymph Node Dissection in Laparoscopy‐Assisted Distal Gastrectomy

Abstract: D2 dissection in LADG can be performed without problems with safety and accuracy, if the surgical team is skilled in the procedures of LADG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 24 publications
3
40
0
1
Order By: Relevance
“…After reading the full texts of the remaining papers, 24 studies were removed as they only reported the outcomes of LG for AGC whereas no controlled or matched cases treated by OG were available. Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…After reading the full texts of the remaining papers, 24 studies were removed as they only reported the outcomes of LG for AGC whereas no controlled or matched cases treated by OG were available. Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…If the feasibility and safety of LGS in the treatment of EGC has been proven, it is also true that several reports have shown the efficacy of LGS in the cure of EGC with results comparable to those of an OGS series [11,12] .…”
Section: Lgs (N = 22) Ogs (N = 25) P Valuementioning
confidence: 99%
“…Furthermore, the timing and patterns of recurrence after laparoscopy-assisted gastrectomy are unknown, although there has been concern regarding the possibility of recurrence related specifically to laparoscopic surgery, such as port-site metastasis or peritoneal metastasis, and concern about inadequate lymph node dissection during laparoscopy-assisted gastrectomy due to its technical difficulty and dependency on surgeon proficiency. [8][9][10][11][12][13][14] The purpose of this retrospective multicenter study is to assess recurrence and its timing, patterns, and risk factors following laparoscopy-assisted gastrectomy as well as survival for gastric cancer based on large-scale data.…”
mentioning
confidence: 99%